ANALISIS PENGARUH PAY OUT, ASSET GROWTH, LAVERAGE, LIKUIDITAS ASSET SIZE, BETA AKUNTANSI TERHADAP BETA PASAR PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sidiq, Ahmad (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
Many chance or choice in investment investors must pay attention matters that influence risk each opportunity exist in side return supposed. Various watchfulness has been done but also vary the result. Author tries to canvass fundamental factors/variables that estimated to influence me market or market risk exist in Indonesia effect exchange. This population is manufacturing business at indonesia effect exchange. Sample total taken chosen method proposive sampling, from existing. Population 148 chosen sample manufacturing business as much as 27 companies. Data that used secondary data shaped financial statement year 2008, share price, federation share price profitabiliti Januari-Desember 2008. Analysis method that used multi regression. Free variable in this watchfulness deviden payout, asset growth, laverage, likuidity, asset size and accountancy beta. While dependent variable is market beta. This watchfulness be of benefit to researchers and academician can give empirical proof hit to what influential fundamental factors towards market beta, so that the result serve the purpose of base wisdom determinant for company. For investor and investor candidate, this working paper result is supposed serve the purpose of consideration in investment decision making. To all academic and researcher, this report result serve the purpose of information ingredient and for watchfulness development furthermore.